1996
DOI: 10.1177/036354659602400104
|View full text |Cite
|
Sign up to set email alerts
|

Grip Lock Injuries to the Forearm in Male Gymnasts

Abstract: We performed an epidemiologic survey to estimate the number of grip lock injuries occurring among male high school and college gymnasts. These injuries occur when dowel grips used by the gymnast become locked on the bar as the gymnast's momentum carries him through the skill being performed. We also questioned injured gymnasts to obtain details of their injuries. Thirty-eight high school coaches reported 17 injuries and 32 college coaches reported 21 injuries for a 10-year period; 36% of the coaches responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Extensor tendon lag and loss of wrist range of motion may occur. 11 Despite these residual deficits, both gymnasts returned to collegiate gymnastics.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Extensor tendon lag and loss of wrist range of motion may occur. 11 Despite these residual deficits, both gymnasts returned to collegiate gymnastics.…”
Section: Discussionmentioning
confidence: 98%
“…Worn and stretched grips 11 are vulnerable to locking. Gymnasts often use the same grips for months to years for a variety of reasons (comfort, superstition, economy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Injuries associated with dowel grips usually occur when the grips used by the gymnasts become locked on the bar as the gymnast's momentum continues on through the skill being performed. 74 Others have suggested that grip lock injuries may be caused by grips that are too large, worn, stretched, or slide up the wrist. 74 It has been suggested that injuries could be prevented by careful maintenance of the equipment to ensure that the grips are in good order and fit the gymnast's hand properly.…”
Section: Performance Techniquementioning
confidence: 99%
“…74 Others have suggested that grip lock injuries may be caused by grips that are too large, worn, stretched, or slide up the wrist. 74 It has been suggested that injuries could be prevented by careful maintenance of the equipment to ensure that the grips are in good order and fit the gymnast's hand properly. 7…”
Section: Performance Techniquementioning
confidence: 99%